Implementation religiosity of servant leadership village head to improve performance village apparatus - Sudirman, Sudirman; Yusnita, Ida; Carolina, Cyntia; Hamdani, Deky; Anugrah, Fadli (International Journal of Enterprise Modelling, 2025)
Village heads play a crucial role in local governance and public service delivery in Indonesia. The concept of servant leadership, emphasizing service, empathy, and community empowerment, has gained attention as an effective leadership model. However, the role of religiosity in shaping servant leadership behavior and its subsequent impact on the performance of village apparatus has not been sufficiently explored. This study aims to examine how religiosity influences the implementation of servant leadership among village heads and how this leadership style, in turn, affects the performance of village apparatus in delivering public services. A quantitative approach was employed, using a survey method with 147 respondents comprising village heads in Kerinci Regency, Jambi Province. The data were analyzed using Structural Equation Modeling (SEM) with AMOS software to test the relationships between dimensions of servant leadership, religiosity, and performance outcomes. The findings indicate that several dimensions of servant leadership—such as altruistic calling, wisdom, persuasive mapping, organizational stewardship, humility, and service—positively and significantly influence servant leadership behavior. Religiosity also has a significant positive effect on servant leadership but does not directly impact performance. Instead, servant leadership mediates the relationship between religiosity and the performance of village apparatus. Servant leadership serves as an effective conduit through which the religiosity of village heads enhances the performance of village apparatus. These findings suggest that integrating religious values into leadership practices can foster more ethical and service-oriented governance in rural communities.